Pengaruh Word of Mouth dan Kualitas Produk terhadap Keputusan Pembelian Dimediasi oleh Brand Image pada Produk Jasa Pembiayaan Kredit Mobil - Hery Winoto Tj; Saparso Saparso; Ardi Kurniaputra Tamzil (Journal of Management and Bussines (JOMB), 2022)
The purpose of this study was to determine the role of brand image in mediating word of mouth and product quality in the purchase decision of PT Maybank Finance's Jambi car loan service product. This research method is descriptive quantitative. This research was conducted using simple random sampling method. Researchers distributed questionnaires to 100 respondents who were customers of PT Maybank Finance in Jambi. The data analysis technique in this study uses Partial Least Square (PLS) with SmartPLS version 3.0 PLS software. The results showed that word of mouth had no effect on purchasing decisions. Product quality has a positive and significant effect on purchasing decisions. Word of mouth does not affect brand image. Product quality has a positive and significant effect on brand image. Brand image has a positive and significant effect on purchasing decisions. In conclusion, positive or negative word of mouth will not affect Maybank Finance's decision to buy an unsecured car. Brand image is unlikely to influence word of mouth on purchasing decisions. Brand image can effectively mediate product quality on purchasing decisions. Keywords: Brand Image, Purchase Decision, Product Quality, Word of mouth